Using Geographical Information System to predict primate crop raiding in Peninsular Malaysia. - Hashim, Nor Rasidah; Abd. Manan, Mohd Shahrudin; Nazli, Mohd Fazlin (2009)
Crop raiding is one of the main primate-human conflicts in Malaysia. In this study, a Geographic Information System (GIS) to predict primate crop raiding susceptibility was developed using land use types and estimated macaque populations as the determining criteria. The susceptibility map showed that most potential crop raiding areas faced low risks. However, this is a likely scale artifact whereby greater accuracies can be achieved using higher resolution spatial data. By including more variables, e.g., elevations, distance from natural predators, the spatial analysis can be more detailed. The private sectors involved in plantations may use the map for their properties management. Furthermore, this susceptibility prediction map of human wildlife conflict can be made for other species for the purpose of wildlife management and conservation.